Tracking ranavirus infections: an integrative review of epidemiological research on pathogen dynamics in anurans - D. D. S. Rodrigues; R. D. C. C. Maia; G. J. B. D. Moura; R. L. M. D. Sousa; J. W. P. Junior (Web Ecology)
Emerging infectious diseases have contributed to the decline in amphibian species around the world. Among them, ranavirus infections have major importance, as they significantly impact biodiversity and frog rearing. This study aims to conduct an integrative review of the recent literature, including epidemiological data on the distribution, prevalence, and circulating species and strains, to identify gaps that may still exist and suggest potential directions for future research. We synthesized data collected from 68 articles found in two scientific databases (Scopus and PubMed), and we provide a situational update on ranavirus infections in anurans. We found relevant reports confirming the high prevalence of this pathogen and the risk it poses, including to endangered species. However, there is still information to be clarified regarding its distribution in different territories and the identification of the species involved in infections.